Efficacy and safety of andexanet alfa for factor Xa inhibitor-associated intracranial haemorrhage - Tsivgoulis, Georgios; Katsanos, Aristeidis H.; Romoli, Michele; Sarraj, Amrou; Krogias, Christos; Karapanayiotides, Theodoros; Theodorou, Aikaterini; Stefanou, Maria Ioanna; Molina, Carlos A.; Themistocleous, Marios; Steiner, Thorsten; Shoamanesh, Ashkan; et al. (Journal of neurology, neurosurgery, and psychiatry, 2025)
Background Current international guidelines suggest andexanet alfa (AA) for the management of factor Xa inhibitor-associated intracranial haemorrhage (ICH). However, those recommendations are based on low-quality evidence and there is uncertainty regarding the net clinical benefit of AA. - Methods We conducted a systematic review and meta-analysis including available randomised controlled clinical trials (RCTs) and observational studies that investigated efficacy and safety of AA compared with usual care for the treatment of factor Xa inhibitor-associated ICH. Good haemostatic efficacy, defined as haematoma expansion of ≤35% or ≤6 mL, was the primary outcome. Secondary efficacy outcomes were excellent haemostatic efficacy (≤20% haematoma expansion) and good functional outcome (modified Rankin Scale scores 0-3) at follow-up, while safety outcomes were mortality and thrombotic events at follow-up. - Results Eighteen studies (1 RCT) were included comprising a total of 1567 patients treated with AA versus 1969 patients receiving usual care. AA was associated with a higher likelihood of good haemostatic efficacy (RR=1.16; 95% CI=1.06 to 1.26) compared with usual care, while excellent haemostatic efficacy (RR=1.04; 95% CI=0.85 to 1.26) and good functional outcome (RR=0.92; 95% CI=0.53 to 1.62) were similar between the two groups. Regarding safety outcomes, similar rates of mortality (RR=0.77; 95% CI=0.56 to 1.04) and thrombotic events (RR=1.20; 95% CI=0.81 to 1.78) were documented. - Conclusions The present meta-analysis suggests AA is associated with improved haemostatic efficacy compared with usual care, with no significant differences observed in functional and safety outcomes. These findings indicate that AA may have a role in the management of factor Xa inhibitor-associated ICH, although further high-quality studies are needed to better define its net clinical benefit.